2015
DOI: 10.3201/eid2110.150678
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mixed Infections withPlasmodiumspp. by PCR, India, 2014

Abstract: In 8 malaria-endemic states in India, mixed Plasmodium spp. infections were detected by PCR in 17.4% (265/1,521) of blood samples that microscopy had shown to contain only P. falciparum. The quality of microscopy must be improved because use of PCR for detection of malaria parasites is limited in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 13 publications
(21 reference statements)
4
44
1
Order By: Relevance
“…This result highlights PCR’s potential for confirming a clinical suspicion of malaria, in spite of being expensive and not available in health centres having limited resources [61]. This study has thus confirmed the importance of PCR-based diagnosis as the norm in future studies concerning P. malariae epidemiology [19, 36, 48, 53]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This result highlights PCR’s potential for confirming a clinical suspicion of malaria, in spite of being expensive and not available in health centres having limited resources [61]. This study has thus confirmed the importance of PCR-based diagnosis as the norm in future studies concerning P. malariae epidemiology [19, 36, 48, 53]. …”
Section: Discussionsupporting
confidence: 70%
“…Such difference has usually been attributed to the fact that mixed-species infection generally implies the predominance of one species, the others having very few parasite forms [36, 53]; this gives an advantage to PCR as TBS has higher detection thresholds [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Both vivax and falciparum infections are reported from all parts of India [12, 13]. Sri Lankans visit different parts of India; many visit the northern and eastern states of India for pilgrimages to sites of Buddhist interest often travelling through the southern states.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based assay has been shown to be more sensitive and specific in the detection and identification of Plasmodium species, and they more readily detect mixed infections [23][24][25][26][27]. They are therefore, useful for epidemiological studies in addition to being an assay of choice in critical situations where confirmatory diagnosis is required.…”
Section: Objectivementioning
confidence: 99%